2012
DOI: 10.13102/scb114
|View full text |Cite
|
Sign up to set email alerts
|

Alocação preferencial de recursos e morfologia de órgãos subterrâneos em plantas resistentes ao fogo em vegetação campestre

Abstract: The underground systems are important for survival of plants and their morphological characteristics have special meaning in environments under disorder. The present study evaluated the existence of preferential allocation of resources in the underground parts of plants resistant to fire and discuss implications of resource allocation and morphology in spatial and temporal dynamics of grassland communities susceptible to fire. The study was restricted to six species of grassland, three monocots (Hypolytrum pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…These structures are lateral stem axes that grow parallel to the soil surface and are capable of forming a new plant (Gonçalves & Lorenzi 2011) or even acting as protective organs. A previous record of stolons for Melastomataceae was provided by Ferreira & Conceição (2012) when they showed that vegetative Rodriguésia 73: e00092022. 2022 growth by stolons aids the regrowth of Marcetia taxifolia (A.St.-Hil.)…”
Section: Discussionmentioning
confidence: 99%
“…These structures are lateral stem axes that grow parallel to the soil surface and are capable of forming a new plant (Gonçalves & Lorenzi 2011) or even acting as protective organs. A previous record of stolons for Melastomataceae was provided by Ferreira & Conceição (2012) when they showed that vegetative Rodriguésia 73: e00092022. 2022 growth by stolons aids the regrowth of Marcetia taxifolia (A.St.-Hil.)…”
Section: Discussionmentioning
confidence: 99%